Sonochemical Synthesis and Properties of YVO4:Eu3+ Nanocrystals for Luminescent Security Ink Applications - Chinh Dung Trinh; Phuong Thi Pham Hau; Thi My Dung Dang; Chien Mau Dang (Journal of Chemistry)
Solutions and redispersible powders of nanocrystalline, europium-doped YVO4, are prepared via a wet chemical method using the ultrasonic processor (sonochemical) and microwave and thermal stirring. From X-ray diffraction (XRD) results, YVO4:Eu3+ nanoparticles synthesized using sonochemical method have better crystallinity than those prepared using thermal stirring and microwave methods exhibiting the tetragonal structure known for bulk material. From field-emission scanning electron microscopy (FE-SEM) and transmission electron microscopy (TEM) results, it is found that the size of nanoparticles is around 25 nm and increasing after annealing at 900°C. From UV-Vis result, there is a peak at 270 nm corresponding to the absorption of VO43− groups. The photoluminescence (PL) results clearly show the strongest red emission peak at the wavelength around 618 nm. The highest luminescent intensity is obtained for the sample prepared by the sonochemical method at pH = 12 and annealing temperature at 900°C for 4 h. The average lifetimes of the Eu3+ ions in the samples annealed at 300, 600, and 900°C for 1 h at 618 nm emission under 275 nm excitation are 0.36, 0.62, and 0.64 ms, whereas sample annealed at 900°C for 4 h has lifetime of 0.70 ms. The security ink, containing synthesized YVO4:Eu3+ nanoparticles, is dispersed in glycerol and other necessary solvents. The experimental security labels are printed by inkjet using the electrohydrodynamic printing technique. The resulting lines represented to the security labels are analyzed by the 3D microscope equipment and UV 20 W mercury lamp with a wavelength of ∼254 nm. The seamless line of the printed security label has the value of the width at ∼230 μm, thickness at ∼0.68 μm, and distance between two adjacent lines at 800 μm. This result is compatible for producing security labels in small size (millimeter) in order to increase security property.